DESAIN PEMBELAJARAN UNTUK MENGEMBANGKAN KECERDASAN MAJEMUK SISWA SEKOLAH DASAR - Alhamuddin Alhamuddin (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2016)
This study aims to examine how to instruction design to optimize the potential of learners. The result of study showed that the design instruction to optimize the learners needs to do several steps, namely: (1) multiple intelligences research; (2) mapping class based on learning style. Furthermore, teachers prepare learning design based on both aspects. Teacher consultation with the supervisor in preparing instructional design based on multiple intelligences, in consultation teacher discusses basic competencies to be taught and strategies in accordance with the tendency of learners in the classroom. The next phase is the observation supervisor in the classroom and the last step is the confirmation. Based on the results of this study, the researchers recommend to teachers to always pay attention and develop the potential that exists within the self-learners early on. Intelligence is not just limited to the intelligence of mathematical logic and language, but also kinesthetic, music, interpersonal, intrapersonal, spatial, and naturalistic intelligence.Keywords: Design, Instructional, Multiple Intelligences